2020
DOI: 10.1093/cdn/nzaa028
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Child Cooking Involvement in Food Preparation and Fruit and Vegetable Intake in a Hispanic Youth Population

Abstract: Background Cooking interventions have been linked to reductions in obesity and improvements in dietary intake in children. Objective To assess whether child cooking involvement (CCI) was associated with fruit intake (FI), vegetable intake (VI), vegetable preference (VP), and vegetable exposure (VE) in children participating in the Texas, Grow! Eat! Go! (TGEG) randomized controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…However, not all families have worse eating habits during the epidemic. Instead, some families see this quarantine period as a perfect opportunity to cook home-cooked food and expose children to more fruits and vegetables to change poor dietary preferences [ 40 , 41 ]. Therefore, it is necessary to provide corresponding advice on the behavior of parents during home isolation for childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all families have worse eating habits during the epidemic. Instead, some families see this quarantine period as a perfect opportunity to cook home-cooked food and expose children to more fruits and vegetables to change poor dietary preferences [ 40 , 41 ]. Therefore, it is necessary to provide corresponding advice on the behavior of parents during home isolation for childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…However, not every household under lockdown experienced such a change in behavioural attitude or food habits as some families considered these unprecedented times as the perfect opportunity to cook homemade food and opted to buy fresher food more than before [8]. Such a positive experience might have a long term effect on children's food intake and preference for fruit and vegetables [9]. Of note, unfortunately a number of jobs were lost during the pandemic leading to financial constrains with a consequential change in grocery shopping to less expensive shelf-stable food.…”
Section: Effect On Dietary Habitsmentioning
confidence: 99%
“…Further, prices of fresh FV have increased at a much faster rate than high fat/sugar foods [14]. Numerous studies have also shown that lack of FV exposure, preference, knowledge and self-efficacy is linked to lower FV intake in children [15][16][17][18]. Evidence-based interventions are needed to improve these psychosocial variables and increase FV access, availability, and intake, particularly in low-income populations.…”
Section: Introductionmentioning
confidence: 99%